Analysis And Extraction Of Mineral Content From Guano In Karst And Non Caves - sambolangi, Arise; Susanto, Agus; Subaer, Subaer; Arsyad, Muhammad (Sahabat Publikasi, 2024)
This study aims to carry out a comprehensive characterization of guano from cave and non-cave environments through a series of mineralogical and chemical analyses. The methodology used includes X-Ray Fluorescence (XRF) analysis to determine the composition of chemical elements, X-Ray Diffraction (XRD) for mineral phase identification, and Scanning Electron Microscopy (SEM) for morphological observations. The objectives of this study are: (1) to analyze the comparison of magnetic mineral properties, (2) to analyze the composition of chemical elements, (3) to analyze the types and phase distribution of magnetic minerals, and (4) to analyze the morphological differences between cave guano and non-cave. Cave guano samples are in the Bat Cave of the Rammang-Rammang Maros Karst Area and for non-cave guano samples are in Kalong Park, Soppeng Regency. The results showed that cave guano had a significantly higher magnetic susceptibility value than non-cave guanos, with variable values ranging from 278.0 x 10-8 m-3 kg to 832.7 x 10-8 m3/kg, while non-cave guano ranged from 23.7 x 10-8 m3/kg to 51.1 x 10^-8 m3/kg. The elemental composition of both types of guano is generally the same, but non-cave guano does not contain vanadium (V). XRD analysis revealed greater mineral phase diversity in cave guano compared to non-cave guanos. SEM confirmed significant morphological differences, with cave guano showing a denser and more uniform microstructure compared to a more heterogeneous structure in non-cave guanos. This research provides new insights into the influence of the environment on the composition and physical properties of guano, which can be helpful in agricultural applications and environmental research.